Effects Of Congenıtally Absent Second Premolars On Facıal And Dental Arch Asymmetry - Sema Yüksel; Tuba Tortop Üçem (Galenos Yayinevi, 1994)
The congenital absence of second premolar introduces an imbalance in maxillar and mandibular dental arch length. The sample consisted of 10 unilateral, 8 bilateral second premolar agenisis patient and 10 subjects without malocclusion for evaluating the asymmetry in normal individuals. The investigation was carried out on anteroposterior radiographs and dental models. On dental models in the group who had unilateral second premolar agenesis in posterior region both in anteroposterior and transversal directions; statistically significant asymmetry was determined. When anteroposterior radiographs were evaluated; mandibular molar cusp values showed statistically significant asymmetry in unilateral second premolar agenesis group.